The Participation of Bidayuh People in Development: A Gender Perspective Analysis - Lyndon, Novel (2004)
The focus of the research is to study the education and employment participation trends of the Bidayuh in Serian and Bau Districts from a gender perspective. The specific objectives are to determine the trend of change in educational attainment between Bidayuh men and women based on 1990 and 2000 census data; to determine whether the survey data on educational attainment are comparable with the trend of change in educational attainment of the year 2000; to determine the trend of change in employment participation between Bidayuh men and women in the three employment sectors namely agriculture, service and manufacturing based on 1990 and 2000 census data; to determine whether the survey data on employment participation are comparable with the trend of change in employment participation of the year 2000; and lastly to explain reasons for differences between educational attainment and employment participation of Bidayuh men and women. iii The study was conducted in four zones of districts of Serian and Bau in Sarawak. The study consisted of two phases. The first phase was on the survey involving a total of 150 households including husbands and wives, who were personally interviewed using structured questionnaire. The data from the first phase were aimed at answering the first, second, third and fourth objectives of the study. The data were analysed using simple statistical tools such as frequencies, percentages, mean, standard deviation and chisquare. The second phase was on an indepth interviews among eight selected informants who were knowledgeable about Bidayuh community. The purpose was to find explanation on the differences between Bidayuh men’s and women’s educational attainment and employment participation. Qualitative data analysis was used for this phase of the study. The trend of change in educational attainment between Bidayuh men and women based on 1990 and 2000 census data shows that the opportunities for education continued to increase but disparity persisted between the two genders. The disparity is seen in terms of accessibility to primary education and attainment in tertiary education. The imbalanced in educational attainment between Bidayuh men and women for 1990 and 2000 census data continued as indicated by the study survey data. Majority of both Bidayuh male and female labour forces continue to concentrate in the traditional and labour-intensive farming between 1990 and 2000. Manufacturing sector that required some level of education, technology and skills, the survey data show that the participation of Bidayuh women in the sector was still lower than Bidayuh men. As in the iv 1990 and 2000 census data, the 2002 survey data show that employment participation in all sectors was continued to differ for Bidayuh men and women. The qualitative data show that there are two reasons why Bidayuh women lag behind the men in educational attainment. The two reasons are cultural influence and historical background that stated Bidayuh women have been long neglected in many aspects of educational opportunities. Similarly, reasons for the differences in employment participation between Bidayuh men and women are traditional gender related division of labour, employer’s bias on gender and the lack of education, skills and training among women. The study poses recommendations for extension, development planners, Sarawak state government, Bidayuh organizations and policy makers. It is hoped that the findings are useful for extension policy and programme planning for rural population with some gender perspectives. The study also recommends that future research should be conducted on the impact of development on the social mobility of Bidayuh men and women.